Simulation of wave processes in liquid under the vibrations of the membrane in the tube - Sergey Evgenyevich Savotchenko; Alexander Semenovich Gorlov (Наука. Инновации. Технологии)
The mathematical model of wave processes in an ideal incompressible liquid inside a cylindrical tube with a vibrating membrane on one end is presented in the article. It is shown that the external force applied to the membrane which is on the one end of the tube initiates its transverse forced vibrations which also initiate pressure disturbance inside the tube. The case of a harmonic external force at fixed frequencies is considered. The results of the influence of external forces of various distributions, including uniform and constant are analyzed. The analytical results for tube with circular and undefined sections are derived. Numerical simulation was carried out for the case of uniformed distribution on the surface of membrane of external harmonic force. It was found that maximum amplitude of forced vibrations is located near the tube edge where the membrane is fixed. As a rule, damping of wave occurs very quickly.